Identificacion de parásitos gastrointestinales en animales silvestres en el centro de rescate de la provincia de El Oro - Guzman Pucha, Samantha Cecibel (Machala : Universidad Técnica de Machala, 2024)
The present study aimed to identify the presence of gastrointestinal parasites in wild animals housed in rescue centers in the province of El Oro, Ecuador. A total of 113 fecal samples from birds (52.2%), mammals (35.4%), and reptiles (12.4%) were analyzed using three coproparasitological techniques: flotation (Faust), sedimentation (Ritchie), and direct examination. A high prevalence of parasitic infections was observed across all species evaluated, with birds exhibiting the highest infection rate (93%), followed by mammals (63%) and reptiles (100%). The most frequently detected parasites in birds were Heterakis spp. (33.9%) and Ascaridia spp. (23.7%). In mammals, Strongyloides spp., Entamoeba spp., and Moniliformis moniliformis were identified, while in reptiles, Oxyuris spp. and Nyctotheroides spp. were detected. The Faust technique proved to be the most effective, identifying 83.1% of positive cases, followed by Ritchie (55.7%) and the direct technique (14.1%). The findings indicate that rescued animals harbor a high parasitic burden, which may compromise their health and well-being. It is recommended to implement comprehensive sanitary management strategies in rescue centers, including routine parasitological monitoring, deworming protocols, and enhanced biosecurity measures. These actions will help prevent parasite transmission and reduce the risk of zoonotic diseases. This study provides critical epidemiological insights for disease surveillance and the development of effective parasite control programs in captive wildlife populations.
El presente estudio tuvo como objetivo identificar la presencia de parásitos gastrointestinales en animales silvestres albergados en el centro de rescate de la provincia de El Oro, Ecuador. Se analizaron 113 muestras fecales de aves (52,2 %), mamíferos (35,4 %) y reptiles (12,4 %) mediante tres técnicas coproparasitológicas: flotación (Faust), sedimentación (Ritchie) y examen directo. Se determina una alta prevalencia parasitaria en todas las especies evaluadas, con aves presentando la mayor frecuencia de infecciones (93%), seguidas de mamíferos (63%) y reptiles (100%). Los parásitos más comunes en aves fueron Heterakis spp. (33,9%) y Ascaridia spp. (23,7%). En mamíferos, se identifican Strongyloides spp., Entamoeba spp. y Moniliformis moniliformis, mientras que en reptiles se hallaron Oxyuris spp. y Nyctotheroides spp. . La técnica de Faust resultó la más eficaz, identificando el 83,1% de los casos positivos, seguida de Ritchie (55,7%) y la técnica directa (14,1%). Los resultados evidencian que los animales rescatados albergan una alta carga parasitaria, lo que puede comprometer su salud y bienestar. Se recomienda implementar estrategias de manejo sanitario en los centros de rescate, incluyendo monitoreo parasitológico rutinario, protocolos de desparasitación y mejores condiciones de bioseguridad. Esto ayudará a prevenir la propagación de infecciones y reducir el riesgo de zoonosis. Este estudio proporciona información relevante para la vigilancia epidemiológica y el desarrollo de planes de control en fauna silvestre en cautiverio.
Keywords: PARASITOS GASTROINTESTINALES; CENTROS DE RESCATE; TECNICAS COPROPARASITOLOGICAS; ZOONOSIS